The Role of Elder (Sambucus nigra) in Arable Farming in the UK - Taylor, Beth (2024)
Elder (Sambucus nigra) is a tree native to Europe which produces large white flower cymes which develop into berries. These flowers and fruit are used primarily in the food and drink industry, but also in cosmetics and medicine. The demand for elder products in the UK is increasing, and not currently being met by UK production. The aim of this project was to understand the management practices key to elder growth, quantify growth and yield between different selections, and comment on its potential contribution to environmental targets (carbon sequestration and biodiversity). Two field experiments were established, investigating the effect of pruning on growth and yield, and soil treatment on establishment success. Pruning showed a consistent decrease in yield, but an increase in pick efficiency (measured by average flower weight) and regrowth, suggesting an increase in quality and productive tree lifespan (longevity). Soil treatment showed inconclusive results but indicated a potential increase in establishment success under compost addition. The elder selections Haschburg and Donau had a high carbon sequestration potential and good early establishment which was reflected in high yield and quality at maturity, and are therefore recommended for growth in the UK. Early assessments of insect abundance surrounding elder indicate a positive effect of elder on biodiversity. Further research into cutting propagation methods, the flavour profile of different selections, and the long-term effects of pruning on yield and quality is recommended to deepen the understanding of the best management techniques and most suitable selections for the UK.